Pengembangan Sistem Manajemen Pendidikan Islam Berbasis Web untuk Transparansi dan Akuntabilitas - Afkar Hanif Syaifuddin (STIKes Ibnu Sina Ajibarang, 2025)
In today's digital era, the development of a web-based education management system is one of the solutions to increase transparency and accountability in Islamic educational institutions. Through a literature approach with qualitative methods, this research aims to provide a clear picture of how information technology can be used to improve efficiency and effectiveness in the management of Islamic education. The ease of gaining access to every aspect of information in the management of education that is easy and fast is needed by student guardians, the community and the government which includes: Administrative and Policy Transparency, Financial Transparency, Academic Transparency and Facilities and Infrastructure Transparency. Any challenges in developing the management system need to be informed and socialized and managed properly to get the best solution from all stakeholders.